Neopulvinaria innumerabilis (Rathvon, 1854), a new species of Coccidae in Serbia - Dervišević, Marina; Graora, Draga (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
In 2016, the species Neopulvinaria innumerabilis (Rathvon, 1854), belonging to the scale insect family Coccidae, was for the first time found in Serbia, in the location Radmilovac on Cornus sanguinea L. It reproduces by gamogenesis, develops one generation annually, and overwinters as a fertilized female on the trunk or branches of its host plant. During this research, the species was detected on five host plants at six locations in Serbia. It feeds by sucking sap from leaves, young shoots and branches of infested plants, causing desiccation of leaves and individual twigs. Four species of its natural enemies were collected and reared from colonies of N. innumerabilis. Two species of parasitoid wasps, Coccophagus lycimnia (Walker) (Aphelinidae) and Metaphycus hageni Daane and Caltagirone (Encyrtidae), were found, while the ladybird Exochomus quadripustulatus L. (Coccinellidae) and the fly Leucopomyia silesiaca (Egger) (Chamaemyiidae) were identified as predators. The most abundant entomophagous species was L. silesiaca.